2016
DOI: 10.1136/bmjspcare-2015-001034
|View full text |Cite
|
Sign up to set email alerts
|

The state of mHealth development and use by palliative care services in sub-Saharan Africa: a systematic review of the literature

Abstract: BackgroundCurrent coverage of palliative care services in sub-Saharan Africa (SSA) remains woefully inadequate, but harnessing mHealth could be one approach to facilitate greater service coverage and engagement with patients with life-limiting progressive disease.AimsA systematic literature review to identify the development and use of mHealth in palliative care services in SSA.Methods13 electronic databases from 1990 to 2015 were searched alongside the manual searching of journals and citation searching of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…In recent years, there has been exploratory research and development of digital health approaches in PC services in SSA 28–30. However, this project seeks to address the lack of a theoretical underpinning to interventions using digital health components in this context.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been exploratory research and development of digital health approaches in PC services in SSA 28–30. However, this project seeks to address the lack of a theoretical underpinning to interventions using digital health components in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews focused on cancer, [21][22][23] others did not limit their inclusion criteria a specific disease. The reviews were carried out by research teams based in the following countries: USA (9), 17,[24][25][26][27][28][29][30][31] UK (6), 16,23,[32][33][34][35] Australia (2), 14,36 Canada (1) 22 Chile (1), 15 Denmark (1) 37 and Brazil (1) 38 .…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 99%
“…Investigating the potential for HPE using mobile technology could, therefore, have particular relevance. [25] Priority # 6 -Quality assurance processes and procedures in health professions education This priority demonstrates the intent of respondents to ensure that educational practices and teaching innovations are carefully monitored and evaluated. Responses provided during the topic generation phase suggested that this focus has to do with being accountable given expectations by stakeholders for the provision of quality education.…”
Section: Enhanced Student Learningmentioning
confidence: 99%